Analisis Dampak Kecerdasan Buatan dalam Peningkatan Efisiensi Pemasaran Digital di Industri E-commerce Indonesia - Debora Oktaviani; Fikra Terisha A; Mashita Ayuni; Tesalonika Sembiring; Wynne Lie; Eryc Yeo (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The e-commerce industry in Indonesia is growing rapidly, but fierce competition and consumer demands require the adoption of advanced technologies to improve the efficiency and effectiveness of digital marketing. Artificial intelligence (AI) offers a solution by enabling content personalisation, process automation and more accurate consumer behaviour prediction. This research, through an integrative literature review, found that AI can increase conversions and sales. However, challenges such as high costs, limited expertise, and ethical issues related to privacy and bias remain. Therefore, appropriate strategies and investment in workforce education are needed to maximise the benefits of AI in Indonesia.